Tailoring education for alpha learners: Harnessing learning styles for maximum learning outcomes - Gacusan, Jenifer C; Dangis, Sanny J; Afalla, Bonimar T (Nurture, 2023)
Purpose: Everyone learns in a different way, depending on what suits them best. Hence, this study explored the learning styles of Alpha learners as perceived by their parents and teachers, with a particular focus on identifying effective teaching techniques that promote engagement and academic success. Design/Methodology/Approach: This descriptive survey was conducted among 52 teachers and 403 parents in Nueva Vizcaya, Philippines. The participants were selected randomly, and a modified teaching-learning styles questionnaire, validated beforehand, was utilized. The collected data were analysed using the mean and standard deviation. Findings: Alpha learners preferred studying on the ground or a couch in various lighting and weather conditions. They pursued task completion and academic excellence while working on their own or under supervision, with external rewards as their motivation. Alpha learners sought consistency and moderate direction. They effectively studied without adult guidance, utilizing a diverse range of tools. Conclusions: Alpha learners exhibit diverse preferences in their learning environment, including seating, lighting, and weather. They are motivated by rewards from outside sources and make an effort for academic success. They like independent or supervised work. They study effectively without adult guidance, utilizing various tools. Effective techniques for Alpha learners include reading, writing, debating, watching, touching, and listening. Research Limitations/Implications: The study is subject to certain limitations, such as its restricted geographical coverage and dependence on self-reported perceptions. To enhance the validity and generalizability of the findings, larger and more diverse samples are required. Subsequent investigations ought to contemplate enlarging the sample size and broadening the participant pool to augment the credibility and universal relevance of the findings. Practical Implications: Clear instructions for parents, strategies to understand and manage children’s traits, and personalized teaching can enhance Alpha learners’ academic performance. Contribution to Literature: This research offers insights into Alpha learners’ styles, preferences, and effective techniques, filling a literature gap. It informs educational practices for their engagement and academic success.